Pengaruh Penerapan Perdagangan Melalui Media Elektronik (E-Commerce) Terhadap Peningkatan Pendapatan Pada Pelaku Usaha Ekonomi Kreatif Di Kota Lubuklinggau - Teresia, Teresia; Asmirawati, Asmirawati; Hidayatullah, Soemarno (Universitas Palangka Raya, 2025)
This research aims to determine the impact of trade through the media electronics on the revenue growth of micro, small and medium enterprises in Lubuk Lingau. The target of this research is MSMEs in Lubuk Linggau. This research using a quantitative approach measured by the linear regression method simple. Respondents in this research are stakeholders interests of MSMEs collaborating in Lubuk Linggau. Samples are determined with random sampling and the number of samples used was 100 SMEs stakeholders. The data used is primary data. Technique data collection using a questionnaire, t-test used for hypothesis testing. The research results show the adoption of commerce through media electronics has a positive effect on increasing business income micro, small and medium in the city of Lubuk Linggau. Introduction to commerce through media electronics in particular have an influence on the changes that occur in elements business and business activities carried out by Lubuk Linggau MSME actors. This can be seen from sales revenue, number of sales, and total income after carrying out sales transactions and marketing activities with using trading media via electronic media.